Enhancing Student Writing and Computer Programming with LATEX and MATLAB in Multivariable Calculus. Issue 6 (2nd July 2016) - Sullivan, Eric; Melvin, Timothy
Abstract: Written communication and computer programming are foundational components of an undergraduate degree in the mathematical sciences. All lower-division mathematics courses at our institution are paired with computer-based writing, coding, and problem-solving activities. In multivariable calculus we utilize MATLAB and LATEX to have students explore mathematics visually, gain programming skills, and write technical reports on their findings. In this article we give a summary of the pedagogy, tools, and logistics of combining technical writing and computer programming with sophomore-level calculus content with the goals of improving student writing, coding, and mathematical understanding.